Off-label underdosed apixaban use in Asian patients with non-valvular atrial fibrillation. (24th May 2021) - Lee, SR; Choi, EK; Park, SH; Jung, JH; Han, KD; Lip, GYH
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In Asian patients with atrial fibrillation (AF), off-label underdosed prescriptions of direct oral anticoagulants (DOACs) are common Purpose: We aimed to compare the effectiveness and safety of off-label underdosed apixaban with on-label standard dose apixaban in Asian patients with AF. Methods: Using the Korean nationwide claims database, we identified patients who prescribed apixaban and did not fulfill the dose reduction criteria of apixaban between January 2015 and December 2017. Multivariable Cox hazard regression model was performed and hazard ratios (HRs) for ischemic stroke, major bleeding (MB), all-cause death, and the composite clinical outcome were analyzed. Results: Compared to patients prescribed on-label standard dose apixaban (n = 4, 194), patients prescribed off-label underdosed apixaban (n = 2, 890) were associated with higher risks of ischemic stroke (adjusted HR [aHR] 1.38, 95% confidence interval [CI] 1.06-1.81), all-cause death (aHR 1.19, 95% CI 1.01-1.39) and the composite clinical outcome (aHR 1.17, 95% CI 1.03-1.34), but with no significant differences in MB between the two groups (Figure). In patients without any dose reduction criteria, off-label underdosed apixaban use was associated with a significantly higher risk of ischemic stroke than on-label standard dose apixaban use (aHR 1.85, 95% 1.25-2.73); however, in patients who had single dose reduction criteria (age ≥80 years, serum creatinine ≥1.5mg/dL, or bodyweight ≤60 kg), off-label underdosed apixaban use did not show a significant overall benefit in the composite clinical outcome compared with on-label standard dose apixaban, but was associated with a higher risk of all-cause death (aHR 1.32, 95% CI 1.07-1.64). Conclusion: Off-label underdosed apixaban use was associated with higher risks of ischemic stroke, all-cause death, and composite clinical outcome and comparable risk of MB compared with on-label standard dose apixaban use. Label-adherence of apixaban dosing should be emphasized to achieve the best clinical outcome for Asian patients with non-valvular AF, especially in those without any dose reduction criteria.